TLR ligands and butyrate increase Pyy expression through two distinct but inter‐regulated pathways. (9th August 2016) - Larraufie, Pierre; Doré, Joël; Lapaque, Nicolas; Blottière, Hervé M.
Summary: The intestinal epithelium is an active barrier separating the host from its microbiota. It senses microbial compounds through expression of a wide range of receptors including the Toll‐like receptors (TLRs). TLRs have been shown to regulate epithelium permeability or secretion of defensin by Paneth cells. However, the expression and function of TLRs in enteroendocrine L‐cells, a specific subtype of intestinal cells secreting PYY and GLP‐1, have not yet been assessed. PYY and GLP‐1 are implicated in regulation of gut motility, food intake and insulin secretion, and are of great interest regarding obesity and type 2 diabetes. Using a cellular model of human L‐cells and a reporter system for NF‐κB activation pathway, we reported functional expression of TLRs in these cells. Stimulation with specific TLR‐agonists increased expression of Pyy but not Proglucagon in an NF‐κB‐dependent manner. Moreover, the effect of TLR stimulation was additive to butyrate, a product of bacterial fermentation, on Pyy expression. Additionally, butyrate also increased Tlr expression, including Tlr4, and the NF‐κB response to TLR stimulation. Altogether, our results demonstrated a role of TLRs in the modulation of Pyy expression and the importance of butyrate, a product of bacterial fermentation in regulation of microbial TLR‐dependent sensing.